Visit Northern Ireland - Oxlade, Chris and Ganeri, Anita (Oxford Heinemann, 2003)
One of a series that introduces countries to young researchers. Each country is considered in terms of its location, weather, shelter, food, landmarks, transport, schools, clothing, recreations, celebrations and culture.
Include Color Illustration, Glossary and Index
Keywords: Northern Ireland -- Geography